2015
DOI: 10.1007/s10840-015-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of left atrial thrombus by intracardiac echocardiography in patients undergoing ablation of atrial fibrillation

Abstract: The results of our staged imaging approach suggest that ICE has a complimentary value in re-screening the LA/LAA for thrombus after a recent negative or equivocal TEE. The presence of SEC during TEE increases the probability of finding a thrombus with ICE, which could potentially be dislodged during catheter manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…It has been shown that intracardiac echocardiography may exclude a thrombus in some patients with positive TEE results; however, the opposite can also occur. 17 Nevertheless, TEE remains the gold standard for the detection of LAA and LA thrombus and the decision whether it is safe to proceed with AF ablation. In our study, TEE allowed to identify the presence of a definite LAA thrombus in 6.6% of the patients and a high probability of a thrombus based on dense echo contrast in 10% of the patients, which is in line with literature data.…”
Section: Patients and Methods Study Populationmentioning
confidence: 99%
“…It has been shown that intracardiac echocardiography may exclude a thrombus in some patients with positive TEE results; however, the opposite can also occur. 17 Nevertheless, TEE remains the gold standard for the detection of LAA and LA thrombus and the decision whether it is safe to proceed with AF ablation. In our study, TEE allowed to identify the presence of a definite LAA thrombus in 6.6% of the patients and a high probability of a thrombus based on dense echo contrast in 10% of the patients, which is in line with literature data.…”
Section: Patients and Methods Study Populationmentioning
confidence: 99%
“…When analyzing retrospective data looking at those who underwent preprocedural TEE and intraprocedural ICE imaging, ICE was able to identify thrombus in seven of 122 patients who were either negative or inconclusive on TEE scan. 32 In a separate study, seven of nine patients who were identified as "equivocal" or as demonstrating "high suspicion" for LAA thrombus on TEE were resolved by ICE imaging, with subsequent successful completion of AF ablation in those patients. 33 ICE imaging is, however, subject to a high degree of variability amongst those manipulating the probe, with optimal views of the LAA originating with the catheter in the right ventricular inflow tract, right ventricular outflow tract, or pulmonary artery all reported.…”
Section: Alternative Strategies: Computed Tomography Intracardiac Ecmentioning
confidence: 98%
“…One study found that when maneuvering the ICE catheter into the right atrium, coronary sinus, and right ventricular inflow tract, ICE was able to identify thrombus in patients with an inconclusive TEE. 1 Another study found that visualization of the LAA improved when the operator viewed from the pulmonary artery. 2 Additional studies concur that ICE can provide detailed imaging of the LAA and may diagnose the presence of thrombus.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…While the LAA may be difficult to visualize with ICE from the right atrium, maneuvering the ICE catheter within the right ventricle and pulmonary artery can provide detailed imaging. One study found that when maneuvering the ICE catheter into the right atrium, coronary sinus, and right ventricular inflow tract, ICE was able to identify thrombus in patients with an inconclusive TEE . Another study found that visualization of the LAA improved when the operator viewed from the pulmonary artery .…”
Section: Introductionmentioning
confidence: 99%